2020
DOI: 10.3390/cancers12061486
|View full text |Cite
|
Sign up to set email alerts
|

Liver Tumor Burden in Pancreatic Neuroendocrine Tumors: CT Features and Texture Analysis in the Prediction of Tumor Grade and 18F-FDG Uptake

Abstract: Pancreatic neuroendocrine tumors (p-NETs) are a rare group of neoplasms that often present with liver metastases. Histological characteristics, metabolic behavior, and liver tumor burden (LTB) are important prognostic factors. In this study, the usefulness of texture analysis of liver metastases in evaluating the biological aggressiveness of p-NETs was assessed. Fifty-six patients with liver metastases from p-NET were retrospectively enrolled. Qualitative and quantitative CT features of LTB were evaluated. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Quantification of total HTL in clinical routine is not routinely performed, and in most cases, tumor load is visually estimated by the radiologist. However, several studies have shown that hepatic tumor burden is an important prognostic imaging marker [ 13 , 64 , 65 ]. Volumetric evaluation of the HTL, as performed by our model, provides useful information on lesion distribution and allows a more realistic quantification of hepatic tumor extent than the (2D) diameter measurements, which are commonly used [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of total HTL in clinical routine is not routinely performed, and in most cases, tumor load is visually estimated by the radiologist. However, several studies have shown that hepatic tumor burden is an important prognostic imaging marker [ 13 , 64 , 65 ]. Volumetric evaluation of the HTL, as performed by our model, provides useful information on lesion distribution and allows a more realistic quantification of hepatic tumor extent than the (2D) diameter measurements, which are commonly used [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…First-order features were frequently selected, yet with conflicting results. Three studies found a lower entropy in high-grade tumours on AP [15,29] with higher uniformity in G3 tumours [15], while a higher entropy was reported in G2/3 on PVP [21]. The abovementioned studies had a low sample size and were of low quality (RQS < 10%).…”
Section: Computed Tomographymentioning
confidence: 93%
“…DL and traditional ML approaches had a similar performance to distinguish pNET grades [38]. Several radiomics features were selected as predictive variables in the constructed models [15,21,24,28,29,35]. Both 2D-and 3D-rendered radiomics features on the portal venous phase (PVP) were predictive for G2/3 [24,52].…”
Section: Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation